AB0159 Prolactin Induces Interferon Regulatory Factor 1 Activation and Histone H4 Hyperacetylation in Primary Monocytes Comparable To Changes Seen in Monocytes from Systemic Lupus Erythematosus Patients. (15th July 2016) - Leung, Y.T.; Sullivan, K.; Shi, L.; Maurer, K.; Song, L.; Petri, M.
Abstract : Background: Epigenetic changes in systemic lupus erythematosus (SLE) offer a potential explanation for the chronicity of disease. We previously found a global increase in histone H4 acetylation (H4ac) in SLE monocytes and 63% of genes with increased H4ac had potential interferon regulatory factor (IRF) 1 binding sites within the 5kb upstream region. We identified specific H4 lysine acetyl groups with significant hyperacetylation in SLE monocytes, as well as an imbalance in specific histone acetyltransferases (HATs) and histone deacetylases (HDACs) in favor of hyperacetylation. IRF1-overexpression drove H4 hyperacetylation and IRF1 recruitment of HAT p300 to target genes increased IRF1 binding to genes with pathological expression in SLE monocytes. IRF1 is highly inducible by prolactin, a hormone implicated in the pathogenesis of SLE: hyperprolactinemia has been reported in 15–33% of SLE patients as compared to 0.4–3% of controls. Prolactin upregulation of IRF1 can lead to H4ac in Nb2 T cells, representing a potential pathological pathway in SLE. Objectives: Prolactin-induced IRF1 activation in primary monocytes and THP1 cells was examined, with the aim to identify IRF1 interactions with histone acetyltransferases (HATs) and histone deacetylases (HDAC) leading to pathological H4ac in SLE. Methods: Flow cytometry for acetylated H4 lysines: K5, K8, K12, K16 were run on the Accuri C6 with isotype controls. H4ac was defined in primary monocytes from 12 normal males under both unstimulated and prolactin-stimulated conditions. Real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) evaluated HAT/HDAC expression in monocytes. IRF1 activation by prolactin in primary monocytes was studied by immunofluorescence microscopy. Interactions of IRF1 and HATs/HDACs were studied in THP1 cells by ChIP analysis. Results: Flow cytometry found significantly increased total H4ac, H4K5, H4K8, H4K12, and H4K16 acetylation ( p =0.01, 0.01, 0.01, 0.002, 0.04) in monocytes stimulated at prolactinoma levels (2000 ng/mL); acetylation at total H4ac, H4K5, H4K8, H4K12, and H4K16 was also increased at pregnancy levels (200 ng/mL).These results were similar to the increase in H4ac seen in SLE monocytes. Immunofluorescence showed translocation of IRF1 from the cytoplasm to the nucleus in prolactin-stimulated primary monocytes at both 200 ng/mL and 2000 ng/mL cells by 1 hr, demonstrating IRF1 activation. qRT-PCR studies of HAT/HDAC expression patterns found increases in PCAF, P300, CBP, GCN5 and ATF2 expression monocytes stimulated by prolactin that was time dependent. Additionally, ChIP assays in THP1 cells suggested that prolactin-stimulation can recruit IRF1 and acetylated H4 to prolactin target genes. Conclusions: These data demonstrate that prolactin stimulation of monocytes induces IRF1 activation and a pattern of acetylated H4 that corresponds to the changes seen in SLE. This helps to explain the known association of prolactinomas with SLE. The identification of candidate HATs that associate with IRF1 in the context of prolactin stimulation may provide for potential therapeutic targets in SLE. Disclosure of Interest: None declared